The Right to Self-Defence: Locke’s Philosophical Approach and Islamic Law - Efendi, Aan; Susanti, Dyah Ochtorina; Cahyaningrum, Lulik Tri; Sudarsono, Sudarsono (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
The right of self-defence is adopted in positive law. Self-defence in forced conditions due to aggression that threatens life, body, or property becomes the basis for exemption from punishment. This study uses the doctrinal type of legal research to justify the right of self-defence from the perspective of Locke's philosophy and Islamic law by collecting, analysing, and interpreting primary and secondary sources of law. In Locke's philosophy, the right to self-defence derives from the executive power of natural law that an individual has in a state of nature to be the judge and executor of natural law against all acts of violation of natural law that threaten their life, freedom, and property. In a political Society formed by mutual consensus to replace the natural state, individuals agree to relinquish the executive power of natural law to a civil government. In a political Society, the civil government is the judge and executor of the law for any dispute between individuals. However, the transfer of Natural Law executive power to the civil government is not absolute because, in certain circumstances that cause the civil government to be unable to protect life, freedom, and property, individuals can reuse their natural law executive power to safeguard themselves. The right of self-defence in a political society becomes a secondary means of self-protection only in circumstances where the civil government cannot protect individuals from threats to life, liberty, and property. Under Islamic law, defending one's own or others' life, honour, and property is the right of every Muslim without relying on a civilian government. Self-defence is carried out in proportion to acts of aggression. Based on Locke's philosophy and Islamic law, adopting the right of self-defence in positive law must have its limits defined to prevent its arbitrary use in an anarchic society